Symposium 1: Supporting Learning Technology: Relationships With Research and Theory - Armitage, Susan; Bryson, Mark; Creanor, Linda; Higgison, Carole; Jenkins, Martin; Ringan, Neil; Newland, Barbara; Prescott, Deborah; Yip, Hennie (Proceedings of the International Conference on Networked Learning, 2004)
This paper focuses on the experiences of a group of learning technology practitioners (the Sandpiper group) faced with the challenge of supporting effective use of learning technologies in institutions. The paper begins with summary of where learning technologists have come from and where they are now. Strategies employed by learning technologists in supporting their own development and practice, as well as that of others, as part of their role are then discussed. The tensions between learning technology practitioners and their relationship to research and theory, which is seen as a key resource to be drawn upon to inform practice, are explored. The paper will conclude by proposing ways in which learning technology practitioners could inform and be informed by research and theory.